Mengembangkan Kreativitas Seni Anak Melalui Kegiatan Membuat Bingkai Foto Keluarga Dari Stik Eskrim - Megasari Megasari; Azizah Amal; Alia Nilawati (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
The researcher aims to develop children's artistic creativity through activities to make family photo frames from ice cream sticks. The type of this research is classroom action research, and the learning model used is the Project-Based Learning model. The subjects of this study were group A children at Baitul Makmur Islamic Kindergarten Banjarmasin. From the observations at Baitul Makmur Islamic Kindergarten, students in group A in the 2021/2022 academic year have relatively low artistic creativity. Based on identifying problems and actions taken in group A of Baitul Makmur Islamic Kindergarten, the researchers obtained the following research data. Before the action the category score reached 16%, in the first cycle it reached 50% and the second cycle reached 83.3%. And with this it can be concluded that efforts to develop children's artistic creativity through activities to make family photo frames from ice cream sticks were declared successful, so this activity can be accepted as a way to develop children's artistic creativity.